2014
DOI: 10.1111/1750-3841.12458
|View full text |Cite
|
Sign up to set email alerts
|

Viability of the Lactobacillus rhamnosus HN001 Probiotic Strain in Swiss‐ and Dutch‐Type Cheese and Cheese‐Like Products

Abstract: The objective of this study was to determine the viability of the probiotic Lactobacillus rhamnosus HN001 in Swiss-type and Dutch-type cheese and cheese-like products (milk fat is substituted by stearin fraction of palm fat) during manufacture, ripening, and storage. The use of the probiotic L. rhamnosus HN001 in Dutch-type cheese and cheese-like products significantly (P = 0.1) changed their chemical composition (protein and fat content) and an insignificant increase (approximately 1.6% in cheese-like product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 32 publications
(37 reference statements)
3
14
0
Order By: Relevance
“…A slight difference in chemical composition was noted between experimental Dutch‐type cheese and control cheese. Our previous findings (Cichosz et al, ) and the results of other studies (Burns et al, ; Ong & Shah, ) validate the above observation. The influence of added bacteria ( Lactobacillus sp.)…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A slight difference in chemical composition was noted between experimental Dutch‐type cheese and control cheese. Our previous findings (Cichosz et al, ) and the results of other studies (Burns et al, ; Ong & Shah, ) validate the above observation. The influence of added bacteria ( Lactobacillus sp.)…”
Section: Discussionsupporting
confidence: 90%
“…Most scientific research papers analyze the viability or survival rates of various bacterial cultures and their influence on physicochemical (glycolytic, lipolytic, and proteolytic) changes in different types of cheese, such as Minas cheese (Dantas et al, 2016), English-type Cheddar (Ganesan et al, 2014), cheese-like products (Cichosz, Aljewicz, & Nalepa, 2014), white cheese (Yerlikaya & Ozer, 2014), cottage cheese (Abadía-García et al, 2013) as well as other dairy products such as yogurts (Ainaz & Ehsani, 2008;Batista et al, 2015;Mani-L opez, Palou, & L opez-Malo, 2014), probiotic beverages (Cusato et al, 2013), fermented milk (De Oliveira, Augusto, Da Cruz, & Cristianini, 2014), ice-creams (Mohammadi, Mortazavian, Khosrokhavar, & Cruz, 2011), and butters (Erkaya, Mustafa, Bayram, & B€ ulent, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…animalis or Lactobacillus casei in whey cheeses can make them safer and extend the shelf life, due to the inhibition of Listeria innocua, Salmonella Enteritidis, Staphylococcus aureus and food spoilage microorganisms such as Pseudomonas aeruginosa and Escherichia coli. Cichosz et al (2014) found higher counts of mesophilic lactic acid bacteria in experimental ripened cheese than in control cheese, and explained that the addition of L. rhamnosus HN001 to experimental cheeses promoted the viability of starter cultures by inhibiting the growth of harmful microflora, such as the coliform group, yeast and mould, and increased the quantity of easily available substrates. Minervini et al (2012) explained that the addition of Bifidobacteria to Gouda and cottage cheeses has a negative effect on the flavour of cheeses, because the concentration of acetic acid was too high and proteolysis too extensive, which decreased consumer acceptability compared to traditional cheeses.…”
Section: Discussionmentioning
confidence: 90%
“…In comparison with fermented milk, cheese is characterized by a higher fat content, a higher buff ering capacity, and a lower water content and activity. Cheese ripening and storage processes off er a more supportive environment for probiotics than fermented dairy products (4,10).…”
Section: Infl Uence Of the Probiotic Lactobacillus Acidophilus Ncfm Amentioning
confidence: 99%
“…8-9 log CFU/g. Daily consumption of 20-25 g of cheese high in probiotics would deliver positive health eff ects (4).…”
Section: Introductionmentioning
confidence: 99%